RELATIONSHIP ROLE OF FAMILY IN PROVISION OF NUTRITION WITH NUTRITIONAL STATUS IN THE ELDERLY IN MOJOKERTO - Suidah, Hartin; Murtiyani, Ninik; Putra, Wahyu Reza (Universitas Airlangga, 2021)
Introduction: Biological changes in the elderly can affect nutritional status including reduced muscle mass, increased fat mass, decreased intestinal mobility, number of missing teeth, decreased sense of sight and reduced capacity of the kidneys to excrete large amounts of water. The impact of these changes is that a balanced nutritional intake is very necessary for the elderly to maintain the quality of life, the healing process and prevent complications of the disease. The family has an important role in maintaining the health status of the elderly through the fulfillment of balanced nutritional needs because the family is the closest party to the elderly. Methods: The design of this research is correlation. This study aims to determine the relationship between the role of the family and the nutritional status of the elderly using a cross sectional approach. The population is elderly aged > 60 in Klinterejo Village, Sooko District, Mojokerto Regency as many as 52 samples with simple random sampling technique. The instrument for measuring variables used questionnaires and KMS (Card Towards Health) sheets. Statistical test using Chi-Square with a value of = 0.05. Results: : The results showed that almost half of the respondents 44.2% had less family roles and as many as 69.2% had poor nutritional status of the elderly. Conclusion: It is expected that the optimal role of the family in providing a balanced menu according to the needs of the elderly so that the nutritional status of the elderly is not in poor condition.